Crime of Human Trafficking in the Arab Region: Research into the Causes and Means of Confrontation - Zerig, Nafissa; Megueddem, Elyassine (Journal of Legal Studies and Researches, 2021)
The study aims to highlighting the global conscience, affecting human rights and fundamental freedoms. It was the largest illicit trade in the world. Highlighting the phenomenon of human trafficking in Arab States, to identify the most important causes, The study confirmed that these States do not constitute an exception to the widespread spread of this crime. This requires more than a law trying to limit it to the need to intensify efforts and adopt action plans and coping strategies.